A case of pulmonary histoplasmosis treated with voriconazole - Xie, Congyi; Yang, Yimin; Wu, Xiaodan; Chen, Zhangzhang; Zhu, Na; Song, Yuanlin; Tong, Lin (The Journal of Infection in Developing Countries, 2022)
Histoplasmosis is an infection caused by the dimorphic fungus Histoplasma capsulatum. The lungs are the most common site of infection, especially in patients with immune deficiency. We report a case of 62-year-old male patient presented with cough for 3 months and had been taking immunosuppressive drugs for 10 years after heart transplantation. Chest CT scan showed multiple pulmonary nodules. Lung tissue biopsy specimen culture suggested fungal infection, and Histoplasma capsulatum was confirmed by next-generation sequencing (NGS) detection. The patient was diagnosed with pulmonary histoplasmosis. After administration of voriconazole for 46 days, the symptom of cough was markedly relieved and the lesions were partly absorbed. After 13 months of treatment, the lesions completely disappeared, and no significant side-effect of voriconazole was observed. To our knowledge, report of voriconazole as the treatment of histoplasmosis is rare, especially in non-endemic areas. Moreover, this case enriches our experience in the adjustment between immunosuppressive and antifungal agents in treating histoplasmosis.